Impedance Spectroscopy: A Versatile Technique to Understand Solution‐Processed Optoelectronic Devices - Ali, Shmshad; Chang, Shuai; Imran, Muhammad; Shi, Qingfan; Chen, Yu; Zhong, Haizheng (Physica status solidi. PSS-RRL. Rapid research letters, 2019)
Solution‐processed optoelectronic devices based on conjugated polymers, colloidal quantum dots (CQDs), halide perovskites, and so on are now emerging as a new‐generation semiconductor technology which prevails its conventional counterparts in terms of low fabrication cost, ease of scalable manufacturing, and abundant material designability. However, the solution‐processed thin films obtained through spin‐coating, spray, inkjet printing, and doctor blading usually suffer from low film quality and a high defect density especially at the interfaces of different functional layers. Currently, the most significant subject is to address the non‐ideal interfaces for achieving improved performance of the devices. Impedance spectroscopy (IS) is a universal technique that can help to examine the charge behavior at the interfaces in an electrochemical or solid‐state multilayered device. Owing to its ability to elucidate the charge transfer, charge transport, and accumulation within the interfaces of electrochemical or multilayered devices with minimal effects to the devices themselves, the use of IS has increased vividly in the last decades. This review provides the basic principles of IS and its applications on solution‐processed optoelectronic devices. Solution‐processed thin film devices usually suffer from low fabrication quality and high defect density especially at the interfaces of different functional layers. This review provides the development of impedance spectroscopy in solution‐processed electrochemical or multilayered devices as a tool to elucidate the charge transfer, transport, and accumulation within the interfaces with minimal effects to the devices themselves.